Gene expression signatures and cardiometabolic outcomes following 8-week mango consumption in individuals with overweight/obesity - Keathley, Justine; de Toro-Martín, Juan; Kearney, Michèle; Garneau, Véronique; Pilon, Geneviève; Couture, Patrick; Marette, André; Vohl, Marie-Claude; Couillard, Charles (Frontiers in Nutrition, 2022)
Background: Little is known about the impact of mango consumption on metabolic pathways assessed by changes in gene expression. Methods: In this single-arm clinical trial, cardiometabolic outcomes and gene expression levels in whole blood samples from 26 men and women were examined at baseline and after 8 weeks of mango consumption and differential gene expression changes were determined. Based on changes in gene expression profiles, partial least squares discriminant analysis followed by hierarchical clustering were used to classify participants into subgroups of response and differences in gene expression changes and in cardiometabolic clinical outcomes following the intervention were tested. Results: Two subgroups of participants were separated based on the resemblance of gene expression profiles in response to the intervention and as responders (n=8) and non-responders (n=18). A total of 280 transcripts were significantly up-regulated and 603 transcripts down-regulated following the intervention in responders, as compared to non-responders. Several metabolic pathways, mainly related to oxygen and carbon dioxide transport as well as oxidative stress, were found to be significantly enriched with differentially expressed genes. In addition, significantly beneficial changes in hip and waist circumference, c-reactive protein, HOMA-IR and QUICKI indices were observed in responders vs. non-responders, following the intervention. Conclusion: The impact of mango consumption on cardiometabolic health appears to largely rely on interindividual variability. The novel transcriptomic-based clustering analysis used herein can provide insights for future research focused on unveiling the origins of heterogeneous responses to dietary interventions. This study was registered with clinicaltrials.gov (NCT03825276).